OASL1 Traps Viral RNAs in Stress Granules to Promote Antiviral Responses - Kang, Ji-Seon; Hwang, Yune-Sahng; Kim, Lark Kyun; Lee, Sujung; Lee, Wook-Bin; Kim-Ha, Jeongsil; Kim, Young-Joon (KOREAN SOC MOLECULAR & CELLULAR BIOLOGY, 2018)
Oligoadenylate synthetase (OAS) protein family is the major interferon (IFN)-stimulated genes responsible for the activation of RNase L pathway upon viral infection. OAS-like (OASL) is also required for inhibition of viral growth in human cells, but the loss of one of its mouse homolog, OASL1, causes a severe defect in termination of type I interferon production. To further investigate the antiviral activity of OASL1, we examined its subcellular localization and regulatory roles in IFN production in the early and late stages of viral infection. We found OASL1, but not OASL2, formed stress granules trapping viral RNAs and promoted efficient RLR signaling in early stages of infection. Stress granule formation was dependent on RNA binding activity of OASL1. But in the late stages of infection, OASL1 interacted with IRF7 transcripts to inhibit translation resulting in down regulation of IFN production. These results implicate that OASL1 plays context dependent functions in the antiviral response for the clearance and resolution of viral infections.
Keywords: I INTERFERON; MDA5; RECOGNITION; LOCALIZATION; COMPLEXES; APOPTOSIS; VIRUSES; PROTEIN; IRF7